QCD sum rule approach to the s->d gamma contribution to the Omega(-)->Xi(-)gamma radiative decay - Nielsen, M.; Barreiro, L. A.; Escobar, C. O.; Rosenfeld, Rogério [UNESP] (American Physical Soc, 1996)
QCD sum rules are used to calculate the contribution of the short-distance single-quark transition s-->d gamma to the amplitudes of the hyperon radiative decay Omega(-)-->Xi(-) gamma. We reevaluate the Wilson coefficient of the effective operator responsible for this transition. We obtain a branching ratio which is comparable to the unitarity limit.